(untitled) (Indian Journal of Animal Production and Management, 2024)
Stocking density is one of the important aspects of housing management. Increased stocking density can influence the skeletal development of broilers negatively and can increase the leg abnormalities thereby generating welfare issue for the same. To study the effect of stocking density, an experiment was conducted at poultry farm, DUVASU, Mathura. Week old turkey poults were distributed randomly on uniform body weight basis in three treatment groups- T-1: standard stocking density (2.5 ft2 per bird); T-2: high stocking density (1.25 ft2 per bird) and T-3: low stocking density (5 ft2 per bird). Tibia and femur were separated from the sacrificed birds and dried in oven at 1050C for 72 hours. There after cooling down to room temperature, the bones were weighed. Digital radiographs of the bones were taken. The dimensions and thickness of the bones were measured. Average femur length was found to be significantly higher (p<0.01) in standard and high SD treatments than the low SD treatment. Radiographic density of Tibia medulla was found to be significantly higher (p<0.01) in low SD treatment than the other two SD treatments.